2021
DOI: 10.47740/486.udsijd6i
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION AND SOURCES OF POLYCYCLIC AROMATIC HYDROCARBONS (PAHs) IN DUST AT FUEL FILLING STATIONS IN THE TAMALE METROPOLIS, GHANA

Abstract: The aim of the study was to identify and quantify the concentrations and potential sources of Polycyclic Aromatic Hydrocarbons (PAHs) present in dust particles at fuel filling stations in the Tamale Metropolis. Sixteen USEPA recognised PAHs were identified after samples were analysed and their potential sources identified using PAH isomeric ratios. Sample extraction was conducted using an Accelerated Solvent Extractor (ASE) and PAH levels in samples were further analysed using the GC-MS system. The total PAHs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, there is a gas station located across the street from the sampling tree that could be contributing to the higher incidence of PAHs. For example, Cobbina et al [ 16 ] carried out a study on the concentration and potential sources of PAHs present in dust particles at gas stations in the Tamale Metropolis, Ghana, in areas with low and high vehicular traffic. They found that petroleum was the largest contributor to PAH emissions in these areas, with a predominance of BaA in both area types.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is a gas station located across the street from the sampling tree that could be contributing to the higher incidence of PAHs. For example, Cobbina et al [ 16 ] carried out a study on the concentration and potential sources of PAHs present in dust particles at gas stations in the Tamale Metropolis, Ghana, in areas with low and high vehicular traffic. They found that petroleum was the largest contributor to PAH emissions in these areas, with a predominance of BaA in both area types.…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies on the contribution of urban sources to the levels of PAHs do not consider non-traffic emission sources, such as cooking emissions [ 12 , 13 , 14 ] and gas stations [ 15 , 16 , 17 ]. Moreover, other non-source factors can also influence the levels of PAHs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation